(untitled) (Superficies y Vacío, 2013)
Nanostructured tin oxide thin films were deposited on silicon and glass slides substrates by reactive DC-Magnetron sputtering using a tin target in a mixture of argon and oxygen gases. The substrate temperature was varied in the range from 53 to 243 oC, keeping the other deposition parameters constant. The tin oxide films were characterized by: Scanning Electron Microscopy, Energy Dispersive Spectrometry, X Ray Diffraction, microRaman spectroscopy and UV-VIS spectroscopy. It was found that the substrate temperature has an effect mainly on the structural, morphological and optical properties of the thin films. At 53 and 90 oC the tetragonal crystalline phase was obtained while a mixture of crystalline phases (o-SnO2 and t-SnO2) was obtained at 148, 185 and 243 °C.